PENEGAKAN HUKUM TERHADAP NELAYAN PELAKU PENGGUNA JARING HELA DI WILAYAH KABUPATEN ROKAN HILIR DITINJAU DARI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 45 TAHUN 2009 TENTANG PERUBAHAN ATAS UNDANG- UNDANG NOMOR 31 TAHUN 2004 TENTANG PERIKANAN - Hidayat, Rahmat; Harahap , Irawan; Oktapani, Slim (LPPM, Universitas Muhammadiyah Riau, 2025)
The implementation of law enforcement in the fisheries sector is very important and strategic in order to support the development of fisheries in a controlled manner and in accordance with the principles of fisheries management. the aim of this research is to analyze how law enforcement is carried out against fishermen who use cast nets in the Rokan downstream district in terms of Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries and to analyze the obstacles and efforts in enforcing the law against fishermen who use them. heaving nets in the downstream Rokan district area are reviewed from Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries, law enforcement processes also considering aspects of guidance and deterrent effects, the imposition of criminal sanctions, the perpetrators are also given an understanding of the impact of the use of illegal fishing gear on the sustainability of the marine environment. The main obstacle faced is limited monitoring infrastructure because the water area that must be monitored is very large, while the number of patrol boats and personnel is limited. Efforts to overcome obstacles in enforcing the law on fly net users in the waters of the downstream Rokan district are by providing special training to improve the ability to identify and handling illegal fishing gear.